2021
DOI: 10.3389/fmicb.2021.644662
|View full text |Cite
|
Sign up to set email alerts
|

Improved Microbial Community Characterization of 16S rRNA via Metagenome Hybridization Capture Enrichment

Abstract: Environmental microbial diversity is often investigated from a molecular perspective using 16S ribosomal RNA (rRNA) gene amplicons and shotgun metagenomics. While amplicon methods are fast, low-cost, and have curated reference databases, they can suffer from amplification bias and are limited in genomic scope. In contrast, shotgun metagenomic methods sample more genomic regions with fewer sequence acquisition biases, but are much more expensive (even with moderate sequencing depth) and computationally challeng… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 70 publications
(92 reference statements)
2
29
0
Order By: Relevance
“…In this series of analyses, it is possible to use all available sequencing reads (see Data Processing and Analysis) (Beaudry et al ., 2021). An reads per kilobase per million mapped reads (RPKM) analysis of our resistance mock community revealed that resistance genes in enriched libraries are sequenced at a much higher sequencing depth than those in unenriched libraries, in all but one resistance class.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this series of analyses, it is possible to use all available sequencing reads (see Data Processing and Analysis) (Beaudry et al ., 2021). An reads per kilobase per million mapped reads (RPKM) analysis of our resistance mock community revealed that resistance genes in enriched libraries are sequenced at a much higher sequencing depth than those in unenriched libraries, in all but one resistance class.…”
Section: Resultsmentioning
confidence: 99%
“…water, clinical built environments, etc.) (Beaudry et al ., 2021). Our ready‐to‐use publicly available bait set is a cost‐effective way to monitor AMR [i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, under specific circumstances, even shotgun metagenomics may not detect certain microorganisms from challenging samples, such as sub-dominant microorganisms or within samples dominated by a large amount of host DNA in host-related environments. In these circumstances, a DNA filtering step or a targeted DNA approach is mandatory [10] ; otherwise, an even deeper shotgun sequencing is necessary, increasing the costs of these analyses. In this context, the hybridization capture targeting of the 16S rRNA gene, or other molecular markers, could be a complementary strategy to explore the microbial community at the species level [11] .…”
mentioning
confidence: 99%
“…In this perspective, we would like to encourage the scientific community to investigate poorly characterized microbiomes through culturomics experiments to gain access to the genome sequence of novel microbial species not already discovered. In this context, it has been shown that unknown microorganisms, also referred to as microbial dark matter, can be easily found in unexplored environments, such as rural human populations, exotic animals, soils, and waters [10,16] . A fundamental step to uncover the complexity of microbiomes is to retrieve genomic sequences not already classified, for example, through the DNA sequencing of putative novel species identified using peptide mass fingerprints by matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) [17] .…”
mentioning
confidence: 99%